Elucidating the Cellular and Molecular Changes of Dopaminergic Neurons by Rotenone-Induced Neurodegeneration in Zebrafish - Ngo, Dung (Université d'Ottawa / University of Ottawa, 2018)
Chemical-induced models have revealed the crucial role of oxidative stress and mito-chondrial dysfunction in the development of Parkinson’s Disease. In this project, firstly, we in-vestigated the mechanism of action of rotenone, a commercialized pesticide that was previously described to reproduce the bradykinetic dopaminergic neurodegeneration symptoms of Parkin-son’s Disease in zebrafish by inhibition of the mitochondrial complex I. We found out that rote-none caused change in the morphology of the zebrafish dopaminergic mitochondrial network. We also observed the altered expression of various genes involves in mitochondrial fusion and fission in response to rotenone exposure. Secondly, to develop the use of adult zebrafish as a toxin-based model for Parkinson’s Disease, we sought to minimize any off-target effects by exposure of rotenone specifically to the brain. We demonstrated that microinjection of rotenone into the forebrain ventricular zone of adult zebrafish decreases the number of dopaminergic neurons. However, behavioural tests suggested that did not translate into locomotor impairment in these fish. Taken together, these results gave us more information about the potential use of zebrafish to study the physiological mechanism leading to dopaminergic degeneration and allow for the development of therapeutic strategies for Parkinson’s Disease.
Keywords: rotenone; complex I inhibitor; Parkinson's disease; dopaminergic neurons